Pro Azure governance and security : a comprehensive guide to Azure policy, blueprints, Security Center, and Sentinel /: a comprehensive guide to Azure policy, blueprints, Security Center, and Sentinel. ([2019]) - Tender, Peter De; Rendon, David; Erskine, Samuel
No abstract available